Novel Pyrroloquinoline Quinone-Modified Cerium Oxide Nanoparticles and Their Selective Cytotoxicity Under X-Ray Irradiation - Elizaveta A. Zamyatina; Olga A. Goryacheva; Anton L. Popov; Nelli R. Popova (Antioxidants)
Ionizing radiation leads to the development of oxidative stress and damage to biologically important macromolecules (DNA, mitochondria, etc.), which in turn lead to cell death. In the case of radiotherapy, both cancer cells and normal cells are damaged. In this regard, the development of new selective antioxidants is relevant. In this study, we first investigated the redox activity of cerium oxide-pyrroloquinoline quinone nanoparticles (CeO2@PQQ NPs) and their cytotoxic effects on normal (mouse fibroblasts, L929) and cancer (mouse adenocarcinoma, EMT6/P) cell cultures. Furthermore, the biological activity of CeO2@PQQ NPs was evaluated in comparison with that of CeO2 NPs and PQQ. The nanoparticles demonstrated pH-dependent reductions in the content of hydrogen peroxide after X-ray exposure. Our findings indicate that viability of EMT6/P cells was more adversely affected by CeO2@PQQ NPs at lower concentrations (0.1 μM) compared to L929. Following X-ray irradiation at a dose of 5 Gy, significant changes in mitochondrial potential (by 29%) and decreased glutathione levels (by 32%) were also observed in EMT6/P culture following irradiation and incubation with CeO2@PQQ NPs. Furthermore, EMT6/P exhibited a 2.5-fold increase in micronuclei and a 2-fold reduction in survival fraction compared to L929. It is hypothesized that CeO2@PQQ NPs may exhibit selective cytotoxicity and radiosensitizing properties against EMT6/P cancer cells. The findings suggest that CeO2@PQQ NPs may have potential as a selective redox-active antioxidant/pro-oxidant in response to X-ray radiation.